Patients’ Experiences of Living with Atrial Fibrillation: A Mixed Methods Study - Marie Stridsman; Anna Strömberg; Jeroen Hendriks; Ulla Walfridsson (Cardiology Research and Practice)
Introduction. Awareness of epidemiological and clinical consequences of atrial fibrillation (AF) has increased, as have disease-related costs. Less attention has been paid to patient-related issues, such as understanding how symptoms, different therapies, and lifestyle adjustments affect daily life. We aimed to describe patients’ experiences of living with AF. Methods. The study design used a parallel convergent mixed methods approach. Patients with AF were included in the SMURF study and referred for catheter ablation. Patients completed questionnaires on symptoms, health-related quality of life, depression, anxiety, and perceived control and were interviewed. The datasets were analysed separately using inductive content analysis and descriptive statistics. Data were merged to obtain a final interpretation. Results. Nineteen patients were interviewed and 18 completed questionnaires. Twelve of the patients were male, mean age 60 years (45–75 years). Inductive qualitative analysis revealed three categories: (i) symptoms and concerns limiting life, (ii) dimensions of worries, and (iii) strategies for management. The most common symptoms were tiredness, weakness/fatigue, and breathlessness during activities, and the most pronounced negative impacts on health-related quality of life (HRQOL) were physically related, shown in the ASTA questionnaire. The most negative SF-36 scores were found in role limitations due to physical health problems and vitality. HADS revealed five patients with some degree of anxiety and four with some degree of depression. Patients had lower scores on perceived control than perceived helplessness in CAS. Patients’ perceived control was higher than their families’, and families experienced more helplessness. Conclusions. The mixed methods design deepens our understanding of challenges faced by patients. Patients experienced a limited ability to perform activities of daily living due to AF which created different kinds of worries that encouraged the use of various strategies to manage their lives. Healthcare providers need to be aware that relationships between patients and their relatives can change, and therefore they need to be supported and integrated into the care system.